2018
DOI: 10.1080/14992027.2018.1425004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a transient noise reduction algorithm on speech intelligibility in noise, noise tolerance and perceived annoyance in cochlear implant users

Abstract: Objective: To evaluate the validity and efficacy of a transient noise reduction algorithm (TNR) in cochlear implant processing and the interaction of TNR with a continuous noise reduction algorithm (CNR). Design: We studied the effects of TNR and CNR on the perception of realistic sound samples with transients, using subjective ratings of annoyance, a speech-in-noise test and a noise tolerance test. Study sample: Participants were 16 experienced cochlear implant recipients wearing an Advanced Bionics Naida Q70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 47 publications
(29 reference statements)
0
15
0
Order By: Relevance
“…The speech intelligibility and reading span data were available from three recent studies of our Department of Otorhinolaryngology: data of Vroegop, Dingemanse, van der Schroeff, Metselaar, and Goedegebure (2017) and data of and Dingemanse, Vroegop, and Goedegebure (2018). From Dingemanse and Goedegebure (2018), we included only 11 participants, because the other participants were already included from .…”
Section: Design and Proceduresmentioning
confidence: 99%
“…The speech intelligibility and reading span data were available from three recent studies of our Department of Otorhinolaryngology: data of Vroegop, Dingemanse, van der Schroeff, Metselaar, and Goedegebure (2017) and data of and Dingemanse, Vroegop, and Goedegebure (2018). From Dingemanse and Goedegebure (2018), we included only 11 participants, because the other participants were already included from .…”
Section: Design and Proceduresmentioning
confidence: 99%
“…(cf. Dingemanse and Goedegebure 2018; Dingemanse, Vroegop, and Goedegebure 2018;Vroegop et al 2017) In all test protocols, a practice run for the sentence-innoise test was performed to make the participants familiar with the voice and the task and to obtain a first estimation of a participants' SRTn. This practice run was followed by a sentence test in quiet, and a practice run for the ANL test to learn the procedure and to follow the instruction carefully.…”
Section: Test Proceduresmentioning
confidence: 99%
“…TNR bb-std was specifically designed to suppress transients with onset times in the order of 1 ms. It features a fast attack time and a high compression ratio to suppress high-intensity transients ( Dingemanse et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the effectivity of TNR bb-std and related algorithms in CI users and listeners with HAs have shown mixed results. Most of them revealed a significant benefit on one or more subjective rating scales, for example, annoyance level of the transient noise, or overall sound comfort ( Keidser et al 2007 ; Liu et al 2012 ; Dingemanse et al 2018 ; Keshavarzi et al 2018 ), but failed to show a significant effect on speech intelligibility ( Keidser et al 2007 ; Dingemanse et al 2018 ). DiGiovanni et al (2011 ) reported no significant effects on any of the subjective ratings tested, but they did find a significant, yet marginal improvement of 4.4% of the speech intelligibility across various noise conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation